Rozwój wielkopowierzchniowych obiektów handlowych w Polsce - Wrzesińska, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
In the paper the development of LSAO in Poland in the span 1990–2007 was discussed. Changes in quantitative structure of stores, concrete mergers and takings over of LSAO as well as productivity of trading area on polish market were presented. Main grown trends of LSAO and its transformation were also discussed